(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2009)
Hanging is one of the most common methods of suicide all over the world. As a method of suicide it is highly lethal in that more than 70% of those who attempt suicide by using this method would die1,2. In few cases, if the person is brought down within very short period of suspension and treated vigorously in hospital, there is always a hope for life.